Failure analysis of laminated composite panels subjected to pure compression - Chin, David Sin Sheng. (2009)
The buckling, postbuckling and ultimate failure behaviour of graphite epoxy laminated rectangular panels with various aspect ratios and stacking sequences were investigated using numerical technique. Nine finite element models based on various combinations of three aspect ratios and three stacking sequences were generated and analysed.